MODEL KOMUNIKASI BENCANA “TABLE TOP EXERCISE” DENGAN KOLABORASI MULTI PIHAK DALAM PEMULIHAN PASCABENCANA - Dwi Nugraheni; Herlina Juni Risma Saragih; Kusuma; Rachmat Setiawibawa; Anwar Kurniadi; Asep Supriatna (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
A “TABLE TOP EXERCISE” DISASTER COMMUNICATION MODEL WITH MULTI-PARTY COLLABORATION IN POST-DISASTERS RECOVERY This research aimed to discuss the disaster communication model through a table top exercise to analyse multi-stakeholder involvement in the implementation of post-disaster rehabilitation and reconstruction activities due to the earthquake in Cianjur in 2022. The disaster impact caused were casualties, damage to infrastructure and housing, as well as massive and significant social, economic and cross-sector losses. Effective disaster communication was a key factor in accelerating post-disaster rehabilitation and reconstruction efforts. This study used a descriptive qualitative method with data collection techniques through Focus Group Discussion (FGD), literature study, and direct observation. The results showed that pentahelix-based multi-stakeholder collaboration, involving the government, business world, academia, community, and media, was a strategic approach in disaster communication. Through the Table Top Exercise, stakeholders could collaborate, coordinate, share information, and play a role in post-disaster recovery. However, the efforts made had not been integrated and run optimally. This research recommended strengthening regulations and socialisation regarding the implementation of post-disaster rehabilitation and reconstruction through the preparation of R3P (Post-Disaster Rehabilitation and Reconstruction Plan) documents collaboratively involving multi-stakeholders, especially pentahelix elements. In addition, it recommended that the establishment of a multi-stakeholder coordination forum could increase the effectiveness of communication and synergy in sustainable post-disaster recovery.